What's Hot in Literacy for 2017: Topics Garnering Attention in 2017. Issue 4 (2nd October 2017) - Cassidy, Jack; Grote-Garcia, Stephanie; Ortlieb, Evan; Loveless, Douglas J.
ABSTRACT: For the past 20 years, Dr. Jack Cassidy and his collaborators have surveyed leaders in the field about the issues in literacy that are receiving attention and those that are no longer in the limelight and presented the findings in the annual "What's Hot, What's Not" column. This tradition has continued into 2017 as 25 literacy leaders and emerging scholars were all interviewed either by phone or in person to determine important topics in the field. The article provides the "hot" and "not hot" topics for 2017 and serves as an important instruction and development tool for literacy educators.